POPULASI & POLA DISTRIBUSI Buchanania arborescens (Blume) Blume (Anacardiaceae) PADA TANAH ULTRA- MAFIK DESA PODI, KECAMATAN TOJO, KABUPATEN TOJO UNA-UNA, SULAWESI TENGAH - Pitopang, Ramadanil; Syam, Nurfadilah; Rasyiid, Mustafid (Biology Department, Mathematics and natural science, Tadulako University, 2024)
This study aims to determine the distribution pattern and population density of Buchanania arborescens (Blume) Blume in Ultramafic Soil, Podi Village, Tojo District, Tojo Una-Una District, Central Sulawesi. Observations were made using the purposive sampling method by establishing five (5) transects 50x10 m in size which there were subplots with size 10x10 m to observe tree (DBH >10 cm), 5x5 m for the sapling and 2x2 m for seedling with a distance of 20 m between transects. The distribution pattern of Buchanania arborescens at the study site was determined by calculating the morbidity index with the results of calculations on seedling phase Id (0.04), sapling Id (0.05) and tree Id (-1.00). The highest density of Buchanania arborescens is in the seedling phase with a value of 200 individuals/Ha, the sapling phase is 176 individuals/Ha and the lowest value is in the tree phase with a total density of 40 individuals/Ha. The results showed that the distribution pattern of Buchanania arborescens for the seedling and sapling phases were clumped, while the tree phase was uniform. The density of Buchanania arborescens was rare density category.